2019
DOI: 10.1002/ffj.3500
|View full text |Cite
|
Sign up to set email alerts
|

A gas Fourier transform infrared spectroscopy methodology for the rapid and accurate discrimination of chicken spoilage through volatiles analysis

Abstract: The discrimination of chicken spoilage is extremely important in order to guarantee the quality and safety of chicken before consumption, and requires an efficient and reliable method. We aimed to find a rapid and accurate method to discriminate the level of spoilage of chicken, and have developed a gas Fourier transform infrared spectroscopy (G‐FTIR) methodology based on analysing volatiles from chicken samples. In this method, the volatiles of chicken samples were first measured by the G‐FTIR spectrometer. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…Colby and Zatman (1973) reported that the accumulation of compounds contributing to the TVB-N is usually seen as a lag phase before an exponential growth period. Similarly, Tan et al (2019) have also reported a lag phase in amine compounds in chicken meat stored at 20 • C.…”
Section: Tvb-nmentioning
confidence: 73%
“…Colby and Zatman (1973) reported that the accumulation of compounds contributing to the TVB-N is usually seen as a lag phase before an exponential growth period. Similarly, Tan et al (2019) have also reported a lag phase in amine compounds in chicken meat stored at 20 • C.…”
Section: Tvb-nmentioning
confidence: 73%
“…The color changes of the indicator were photographed and are presented in Figure 8 . This alteration in color is associated with the deprotonation of anthocyanins caused by TVB-N compounds produced during the degradation process [ 39 ]. The color values as determined by the colorimeter are listed in Table 2 .…”
Section: Resultsmentioning
confidence: 99%